2006
DOI: 10.1128/aac.50.3.874-879.2006
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Telbivudine following Oral Administration of Escalating Single and Multiple Doses in Patients with Chronic Hepatitis B Virus Infection: Pharmacodynamic Implications

Abstract: The pharmacokinetics of telbivudine were evaluated in adult patients with chronic hepatitis B virus (HBV) infection following once-daily oral administration at escalating doses of 25, 50, 100, 200, 400, and 800 mg/day for 4 weeks. Telbivudine was rapidly absorbed after oral administration, with the median times T max to the maximum plasma concentration (C max ) ranging from 0.8 to 3.0 h postdosing across cohorts. Single-dose and steady-state maximum C max s and the areas under the plasma concentration-time cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 7 publications
6
40
0
Order By: Relevance
“…In addition, data from a phase I/II trial with HBV-infected patients showed that telbivudine exhibited doseproportional pharmacokinetics and an exposure-related viral response, with nearly maximum antiviral effects achieved with telbivudine doses in the range of 400 to 800 mg/day (10,18). No dose-limiting toxicities were observed in that trial over the dose range studied, 25 to 800 mg/day (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, data from a phase I/II trial with HBV-infected patients showed that telbivudine exhibited doseproportional pharmacokinetics and an exposure-related viral response, with nearly maximum antiviral effects achieved with telbivudine doses in the range of 400 to 800 mg/day (10,18). No dose-limiting toxicities were observed in that trial over the dose range studied, 25 to 800 mg/day (10).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic studies with healthy subjects and HBVinfected patients demonstrated that following oral dosing, telbivudine is rapidly absorbed, with maximum plasma concentrations (C max ) reached within 1 to 3 h (16,17,18,19). Following intravenous and oral administration of telbivudine at 10 mg/kg to cynomolgus monkeys, 77.0% and 36.6% of the administered drug, respectively, was eliminated in the urine within 14 days (unpublished data).…”
mentioning
confidence: 99%
“…Incorporation of the 5Ј-triphosphorylated telbivudine into viral DNA causes DNA chain termination, resulting in inhibition of HBV replication (1). Recent clinical trials in adults with chronic HBV have established that once-daily telbivudine is well tolerated by patients and exhibits dose-dependent potent antiviral activity (12,13,21).…”
mentioning
confidence: 99%
“…This suggests that myalgia is dose-dependent. Other studies [24][25][26][27] have shown that telbivudine plasma concentration is correlated with dosage when in the range 200-600 mg/d. As a result of the long half-life of this drug, a dose of 600 mg twice daily may lead to drug accumulation.…”
Section: Risk Factors Related To Telbivudine Treatmentmentioning
confidence: 99%